Infinium Monkeys: Infinium 450K Array for the Cynomolgus macaque (Macaca fascicularis). Issue 7 (1st July 2014) - Ong, Mei-Lyn; Tan, Peck Yean; MacIsaac, Julia L; Mah, Sarah M; Buschdorf, Jan Paul; Cheong, Clara Y; Stunkel, Walter; Chan, Louiza; Gluckman, Peter D; Chng, Keefe; Kobor, Michael S; Meaney, Michael J; et al.
Abstract: The Infinium Human Methylation450 BeadChip Array (Infinium 450K) is a robust and cost-efficient survey of genome-wide DNA methylation patterns. Macaca fascicularis (Cynomolgus macaque) is an important disease model; however, its genome sequence is only recently published, and few tools exist to interrogate the molecular state of Cynomolgus macaque tissues. Although the Infinium 450K is a hybridization array designed to the human genome, the relative conservation between the macaque and human genomes makes its use in macaques feasible. Here, we used the Infinium 450K array to assay DNA methylation in 11 macaque muscle biopsies. We showed that probe hybridization efficiency was related to the degree of sequence identity between the human probes and the macaque genome sequence. Approximately 61% of the Human Infinium 450K probes could be reliably mapped to the Cynomolgus macaque genome and contain a CpG site of interest. We also compared the Infinium 450K data to reduced representation bisulfite sequencing data generated on the same samples and found a high level of concordance between the two independent methodologies, which can be further improved by filtering for probe sequence identity and mismatch location. We conclude that the Infinium 450K array can be used to measure the DNA methylome of Cynomolgus macaque tissues using the provided filters. We also provide a pipeline for validation of the array in other species using a simple BLAST-based sequence identify filter.